Assessment of EFL Student Teachers’ Performance in Practicum - PATINVOH AGBAYAHOUN, JUVENALE (My University, 2014)
This study investigates the procedure followed to assess student teachers’ performance in the practicum component of an EFL teacher training program in Benin. It examines the criteria whereby supervisors evaluate student teachers’ teaching competence in the selected secondary schools where the practicum takes place. The study also attempts to uncover the student teachers’ perceptions and understanding of the assessment procedure in the practicum as a whole in order to determine whether or not the secondary school supervisors and the student teachers are aware of the competencies targeted by the teacher training college for the practicum. The findings reveal the non-existence of a clearly defined list of competencies and of performance criteria for the TEFL practicum. As a result, the secondary school supervisors resort to their past training and teaching experiences to make decisions about trainees’ assessment, which makes the assessment procedure obscure and subjective from the trainees’ points of view. Suggestions are made in the study for a better assessment procedure in the practicum component of the EFL teacher training program.
Keywords: TEFL practicum; teaching competence; teacher performance; teacher perception; performance assessment in practicum.